2D amorphous MoS3 nanosheets with porous network structures for scavenging toxic metal ions from synthetic acid mine drainage. Issue 32 (31st July 2019) - Fu, Weng; Yang, Siyuan; Yang, Hong; Guo, Bao; Huang, Zhiqiang
Abstract : 2D amorphous MoS3 nanosheets with a unique porous network structure for heavy metal adsorption. Abstract : This is the first time that two-dimensional (2D) amorphous MoS3 nanosheets were prepared by the exfoliation of the bulk amorphous MoS3 material in dimethylformamide (DMF) solvent under ultrasonic irradiation. The obtained 2D amorphous MoS3 nanosheets show a unique porous network structure, which is quite different from that of 2D crystalline MoS2 nanosheets. The XPS and Raman results reveal that the structure of 2D amorphous MoS3 nanosheets contains high levels of active sulphide groups with unsaturated bonds, suggesting that this material can be applied as an efficient heavy metal scavenger in the field of environmental remediation. The interaction mechanisms between metal ions and specific sulphide groups on 2D amorphous MoS3 nanosheets have been discussed. The feasibility of toxic metal remediation (Cu, Cd and Hg) from a synthetic acid mine drainage solution has been proven. The results suggest that 2D amorphous MoS3 nanosheets as a new member of the 2D material family will have promising applications in environmental protection.